Sunbed use in German adults: Risk awareness does not correlate with behaviour - Schneider, Sven; Zimmermann, Susanne; Diehl, Katharina; Breitbart, Eckhard W.; Greinert, Ruediger (Acta Dermato-Venereologica, 2009)
In Europe, little is known about the prevalence of indoor tanning. The aims of this study were therefore to estimate the prevalence of sunbed use and to identify risk groups and motives in a population-based survey. The cross-sectional "SUN-Study 2008" ("Sunbed-Use: Needs for Action-Study 2008") was conducted in 2008. A total of 500 adults, aged 18-45 years, were randomly selected and asked about their indoor tanning practices, their motivation and risk perception, and the compliance of staff with international sunbed use recommendations. Forty-seven percent of subjects reported having visited an indoor tanning facility at least once in their lives. Prevalence of use was not reduced in risk groups for skin cancer. Risk awareness of users equalled that of non-users. The poor quality of services and advice provided by many solariums was alarming. It can be concluded that appropriate measures to change tanning habits need to be identified. Legal regulations could be one option. © 2009 The Authors.
CRIS-Team Scopus Importer:2021-12-06
Keywords: Health behaviour; Melanoma; Motivation; Prevention; Risk factors; Sunburn